Pengolahan Sampah Organik dari Limbah Rumah Tangga Menjadi Produk Eco-Enzyme di Desa Dalaka Kabupaten Donggala - Ruslan Ruslan; Khairuddin Khairuddin; Jaya Hardi (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the knowledge and skills of housewives in Dalaka Village by processing organic waste from household waste into eco-enzyme products. This service was implemented through counseling and training in making fermenters and making eco-enzymes with simple and inexpensive methods. The production of eco-enzymes was done using the ratio of 3kg of organic waste, 1 kg of brown sugar, and 10L of water. The instrument for evaluating this activity used a satisfaction questionnaire form and was analyzed descriptively. The results of this dedication showed that partners could understand well the technology introduced and apply it. The resulting eco-enzyme product had a brown color and a distinctive sour aroma. The average level of participant satisfaction was in the "satisfied" range. Utilization of organic waste from household